1160. Treatment-Emergent Viral Variants in the Phase 3 TACKLE Trial Investigating Efficacy and Safety of AZD7442 (Tixagevimab/Cilgavimab) for the Treatment of Mild to Moderate COVID-19 in Adults. (15th December 2022) - Kijak, Gustavo H; Ahani, Bahar; Arbetter, Douglas; Brady, Tyler; Chuecos, Fernando; Gopalakrishnan, Vancheswaran; Roe, Tiffany L; Schuko, Nicolette; Richard Hobbs, F D; Padilla, Francisco; Kelly, Elizabeth J; Montgomery, Hugh; et al.
Abstract: Background: AZD7442 (tixagevimab/cilgavimab) is a combination of neutralizing monoclonal antibodies (mAbs) that bind to distinct epitopes on the SARS-CoV-2 spike protein, with neutralization activity against variants including Omicron. In the Phase 3 TACKLE study, AZD7442 significantly reduced severe disease progression or death and was well-tolerated through Day 29. Viral evolution during treatment has the potential for resistance selection, such as variants exhibiting reduced mAb binding. We report genotypic analysis and phenotypic characterization of variants identified over 15 days after AZD7442 treatment in TACKLE. Methods: In TACKLE (NCT04723394), non-hospitalized adults with mild to moderate COVID19 were randomized and dosed ≤7 days from symptom onset with a single 600-mg AZD7442 dose (2 consecutive intramuscular injections, 300 mg of each antibody; n=452) or placebo (n=451). Next-generation sequencing of the spike gene was performed on SARS-CoV-2 reverse-transcription polymerase chain reaction–positive nasal swabs (at baseline and Days 3, 6, and 15). SARS-CoV-2 lineages were assigned using spike nucleotide sequences. Amino acid substitutions, insertions, and deletions were analyzed at allele fractions (AF, % of sequence reads represented by mutation) ≥25% and 3–25%. Results: Baseline spike sequences were available from 744 participants (82.4%) (AZD7442, n=380; placebo, n=364); 87% of sequences corresponded to variants of concern/interest; these were balanced between AZD7442 and placebo groups (Table 1). Treatment-emergent (post-dosing) viral variants were rare, with 11 (4.5%) AZD7442 and 3 (1.3%) placebo participants showing the emergence of ≥1 mutation at tixagevimab/cilgavimab binding sites, with an AF ≥25% (Table 2). At AF 3–25%, treatment-emergent viral variants in the AZD7442 binding site were observed in 16 (6.6%) AZD7442 and 15 (6.5%) placebo participants. Conclusion: Following AZD7442 treatment, low levels of SARS-CoV-2 variants bearing mutations at tixagevimab/cilgavimab binding sites were identified. These data indicate that combination of two antibodies creates a high genetic barrier for resistance, supporting the use of mAb combinations that bind to distinct epitopes for the treatment of COVID-19. Disclosures: Gustavo H. Kijak, PharmD PhD, AstraZeneca: Employee|AstraZeneca: Stocks/Bonds Bahar Ahani, BSC, AstraZeneca: Employee|AstraZeneca: Stocks/Bonds Douglas Arbetter, MPH, AstraZeneca: Employee|AstraZeneca: Stocks/Bonds Tyler Brady, MS, AstraZeneca: Employee|AstraZeneca: Stocks/Bonds Fernando Chuecos, BS, AstraZeneca: Employee|AstraZeneca: Stocks/Bonds Vancheswaran Gopalakrishnan, PhD, AstraZeneca: Employee|AstraZeneca: Stocks/Bonds Tiffany L. Roe, B.S., AstraZeneca: Employee|AstraZeneca: Stocks/Bonds Nicolette Schuko, MS, AstraZeneca: Employee|AstraZeneca: Stocks/Bonds F.D. Richard Hobbs, FMedSci, AstraZeneca: Grant/Research Support|AstraZeneca: Principal investigator|NIHR Applied Research Collaboration, Oxford Thames Valley: Director|Oxford BRC and NIHR MedTech: Investigator|UKRI and NIHR: Grant/Research Support Francisco Padilla, MD, Amgen: Grant/Research Support|Amgen: Personal fees|AstraZeneca: Grant/Research Support|AstraZeneca: Personal fees|Boehringer Ingelheim: Grant/Research Support|Boehringer Ingelheim: Personal fees|Ferrer: Grant/Research Support|Ferrer: Personal fees|Kowa: Grant/Research Support|Kowa: Personal fees|Medix: Grant/Research Support|Medix: Personal fees|Merck Sharp and Dohme: Grant/Research Support|Merck Sharp and Dohme: Personal fees|Novartis: Grant/Research Support|Novartis: Personal fees|Pfizer: Grant/Research Support|Pfizer: Personal fees|Sanofi: Grant/Research Support|Sanofi: Personal fees|Servier: Grant/Research Support|Servier: Personal fees|Silanes: Grant/Research Support|Silanes: Personal fees Elizabeth J. Kelly, PhD, AstraZeneca: Employee|AstraZeneca: Stocks/Bonds Hugh Montgomery, MD, AstraZeneca: Advisor/Consultant|Millfield Medical Ltd: Advisor/Consultant|UK National Institute for Health Research's Comprehensive Biomedical Research Centre at University College London Hospitals: Grant/Research Support Katie Streicher, PhD, AstraZeneca: Employee|AstraZeneca: Stocks/Bonds.